2009
DOI: 10.1007/s00192-009-0934-6
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Prolapse Quality-of-Life Questionnaire (P-QoL) in Portuguese version in Brazilian women

Abstract: The Portuguese version of the P-QoL questionnaire is a valid and reliable instrument to assess quality of life in Brazilian women with pelvic organ prolapse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
24
0
5

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 15 publications
6
24
0
5
Order By: Relevance
“…The results correlate with the findings of other validation studies which indicated statistical significant differences between the scores of symptomatic and asymptomatic patients. Lenz et al [11] and De Oliveira et al [12] also found the domain scores of 'general health perceptions' to be similar for both groups, because of the fact that this category consists of only one question and can be affected by symptoms or diseases not related to POP. A finding significant to this study was the lack in differences in scores relating to 'prolapse impact' .…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The results correlate with the findings of other validation studies which indicated statistical significant differences between the scores of symptomatic and asymptomatic patients. Lenz et al [11] and De Oliveira et al [12] also found the domain scores of 'general health perceptions' to be similar for both groups, because of the fact that this category consists of only one question and can be affected by symptoms or diseases not related to POP. A finding significant to this study was the lack in differences in scores relating to 'prolapse impact' .…”
Section: Discussionmentioning
confidence: 92%
“…The questionnaire covers various domains of life which include general health, prolapse impact, role limitations, physical limitations, social limitations, personal relationships, emotional problems, sleep/energy disturbances and prolapse severity. [9] The P-QOL has been successfully translated into eight languages, and includes versions in Italian, [5] Turkish, [10] German, [11] Portuguese, [12] Dutch, [2] Thai, [8] and most recently Persian. [13] The lack of a validated Afrikaans questionnaire investigating QOL in patients experiencing prolapse limits studies and effective outcome measurement in Afrikaans-speaking patients in SA.…”
mentioning
confidence: 99%
“…Since the prolapse may affect different aspects of a woman's life, by limiting psychological, physical, social and sexual domains of her life, the severity of these limitations and their impact on the quality of patient life becomes an important source of information for a surgeon while deciding whether a woman needs to be treated or what kind of therapy would be the most appropriate in her case. As it was shown by Digesu et al [2], who developed the P-QoL questionnaire, and confirmed by many authors who proved its validity [4][5][6], the questionnaire is a reliable instrument in a routine clinical practice and treatment follow-up. Regardless of many quality-of-life questionnaires for women suffering from urinary incontinence, there is no validated questionnaire to assess QoL of Polish-speaking women with POP.…”
Section: Discussionmentioning
confidence: 68%
“…The P-QoL questionnaire was translated and validated in several languages [2][3][4][5][6][7][8][9]. The steps of translation and validation were similar in each language.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation